Increased functional connectivity between superior colliculus and brain regions implicated in bodily self‐consciousness during the rubber hand illusion. Issue 2 (24th October 2014) - Olivé, Isadora; Tempelmann, Claus; Berthoz, Alain; Heinze, Hans‐Joachim
Abstract Bodily self‐consciousness refers to bodily processes operating at personal, peripersonal, and extrapersonal spatial dimensions. Although the neural underpinnings of representations of personal and peripersonal space associated with bodily self‐consciousness were thoroughly investigated, relatively few is known about the neural underpinnings of representations of extrapersonal space relevant for bodily self‐consciousness. In the search to unravel brain structures generating a representation of the extrapersonal space relevant for bodily self‐consciousness, we developed a functional magnetic resonance imaging (fMRI) study to investigate the implication of the superior colliculus (SC) in bodily illusions, and more specifically in the rubber hand illusion (RHi), which constitutes an established paradigm to study the neural underpinnings of bodily self‐consciousness. We observed activation of the colliculus ipsilateral to the manipulated hand associated with eliciting of RHi. A generalized form of context‐dependent psychophysiological interaction analysis unravelled increased illusion‐dependent functional connectivity between the SC and some of the main brain areas previously involved in bodily self‐consciousness: right temporoparietal junction (rTPJ), bilateral ventral premotor cortex (vPM), and bilateral postcentral gyrus. We hypothesize that the collicular map of the extrapersonal space interacts with maps of the peripersonal and personal space generated at rTPJ, vPM and the postcentral gyrus, producing a unified representation of space that is relevant for bodily self‐consciousness. We suggest that processes of multisensory integration of bodily‐related sensory inputs located in this unified representation of space constitute one main factor underpinning emergence of bodily self‐consciousness. Hum Brain Mapp 36:717–730, 2015.. © 2014 Wiley Periodicals, Inc.